Who should I listen to? Gender and age effects in how group norms relate to adolescents' intergroup relations and prejudiced attitudes - Klein, Sydney; Brenick, Alaina; Kelly, Megan Clark; Mohamed, Hla; Scally, Kaila; Andrade, Sophia (Frontiers in Developmental Psychology, 2025)
IntroductionWhen thinking about intergroup exclusion, adolescents weigh prosociality and fairness with the influences of their families and peers. However, research has yet to address whether these group norms influence youth similarly across gender and age. The current study addresses this gap in the literature by assessing and interaction between subjective outgroup norms and developmental period on youth's evaluations of exclusion and their justifications for those evaluations, and does so within an understudied dynamic between Jewish American and Arab American adolescents.MethodsThis study assessed whether gender and age moderate the influence of parent and peer outgroup attitudes on 241 Jewish American 9th graders' (MAge9thGrade = 14.18; SD = 0.42) and 12th (MAge12thGrade = 17.21; SD = 0.43) acceptance and reasoning about intergroup exclusion toward Arab American peers.ResultsResults revealed that gender was associated with the malleability to influence of 9th graders' attitudes, whereas their 12th grade counterparts were unaffected. Furthermore, positive peer groups served as a buffer against the detrimental effects of parents' prejudiced attitudes.DiscussionAge and context play a meaningful role in adolescents' evaluation and justifications of outgroup social exclusion. These findings contribute to the understanding of the development of prosocial reasoning and behaviors in adolescence.